Sensor location affects skeletal muscle contractility parameters measured by tensiomyography - Schwiete, C.; Roth, C.; Braun, C.; Rettenmaier, L.; Happ, K.; Langen, G.; Behringer, M. (PLOS ONE, 2023)
Tensiomyography (TMG) is a non-invasive method for measuring contractile properties of skeletal muscle that is increasingly being used in research and practice. However, the lack of standardization in measurement protocols mitigates the systematic use in sports medical settings. Therefore, this study aimed to investigate the effects of lower leg fixation and sensor location on TMG-derived parameters. Twenty-two male participants underwent TMG measurements on the m. biceps femoris (BF) in randomized order with and without lower leg fixation (fixed vs. non-fixed). Measurements were conducted at 50% of the muscle`s length (BF-mid) and 10 cm distal to this (BF-distal). The sensor location affected the contractile properties significantly, both with and without fixation. Delay time (Td) was greater at BF-mid compared to BF-distal (fixed: 23.2 ± 3.2 ms vs. 21.2 ± 2.7 ms, p = 0.002; non-fixed: 24.03 ± 4.2 ms vs. 21.8 ± 2.7 ms, p = 0.008), as were maximum displacement (Dm) (fixed: 5.3 ± 2.7 mm vs. 3.5 ± 1.7 mm, p = 0.005; non-fixed: 5.4 ± 2.5 mm vs. 4.0 ± 2.0 mm, p = 0.03), and contraction velocity (Vc) (fixed: 76.7 ± 25.1 mm/s vs. 57.2 ± 24.3 mm/s, p = 0.02). No significant differences were revealed for lower leg fixation (all p > 0.05). In summary, sensor location affects the TMG-derived parameters on the BF. Our findings help researchers to create tailored measurement procedures in compliance with the individual goals of the TMG measurements and allow adequate interpretation of TMG parameters.